Nurses' experiences of provision of discharge education to heart failure patients in a tertiary hospital in Saudi Arabia - Rabele, Lirontso Margaret (Stellenbosch : Stellenbosch University, 2026)
Thesis (MNur)--Stellenbosch University, 2025.